Biofilme estafilocócico: prevenção, detecção da produção e determinação do perfil de resistência a antimicrobianos - Oliveira, Adilson de [UNESP] (2014)
Staphylococcus aureus, together with other coagulase-negative staphylococci (CoNS), is an important pathogen that causes nosocomial infections associated with the use of implantable devices. The most important factor in the pathogenesis of staphylococcal infections associated with these devices is the ability of the pathogen to form a biofilm, which protects bacteria against the host immune system and against the action of antimicrobial drugs. The main component of staphylococcal biofilms is polysaccharide intercellular adhesin (PIA), which is encoded by the icaADBC operon. The objectives of this study were to investigate the structure of biofilms of different Staphylococcus species, to evaluate the effect of antibiotics used to treat these infections on planktonic and biofilm cels, and to identify alternatives for the prevention of biofilm formation. A total of 200 Staphylococcus spp., including 50 S. aureus and 150 CoNS strains (50 S. epidermidis, 20 S. haemolyticus, 20 S. warneri, 20 S. hominis, 20 S. lugdunensis and 20 S. saprophyticus), isolated from patients seen at the University Hospital of the Botucatu School of Medicine (HC-FMB), were studied. The presence of the icaADBC genes was investigated by the polymerase chain reaction (PCR) and their expression was determined by reverse transcriptase-PCR (RT-PCR). Biofilm formation was evaluated using the phenotypic method of adherence to borosilicate tubes and polystyrene plates. The minimum inhibitory concentration (MIC) of oxacillin, vancomycin, erythromycin, gentamicin, linezolid and sulfamethoxazole-trimethoprim for planktonic and biofilm cells was determined by the broth microdilution method. The effect of RNA-inhibiting peptide (RIP) on the prevention of biofilm formation was tested using bacterial cultures grown in TSB-2% glucose containing catheter tips and visualization by scanning electron microscopy and on polystyrene plates. The icaA gene was detected by PCR in 97 (48.5%) ...